Macroalgae associated with Tanjung Adang Laut seagrass meadow, Sungai Pulai estuary, Johor, Malaysia, from 2015 to 2017 - Zakaria, Muta Harah; Bujang, Japar Sidik; Syed, Nurul Nur Farahin; Ramaiya, Shiamala Devi; Lau, Emmclan Sheng Hann; K., Hayashizaki (University of the Philippines Visayas, 2019)
The seagrass meadow in Tanjung Adang Laut shoal in Johor, Malaysia, harbors a diverse macroalgal species assemblage with a wide range of forms from the simple crustose, foliose and filamentous to complex structures. Their co-existence with seagrasses contributes significantly to the structure and function of the ecosystem. A monthly survey of macroalgae using quadrats at 10 m intervals along two fixed-line transects and random quadrat samplings around the shoal was conducted from 2015 to 2017, during land reclamation in a nearby area, to assess their species diversity, life forms, and coverage. A total of 38 species of macroalgae comprising 16 Chlorophyta, 7 Ochrophyta, and 15 Rhodophyta were present with the majority of macroalgae being epipelic. In 2015 and 2016, the macroalgae attained maximum coverage from February to May with 94–100% and 88–100% coverage, respectively, and declined in June. In 2017, the macroalgae massively proliferated from February to April with 83–100% coverage and declined in May. Amphiroa fragilissima was the dominant species followed by Hydropuntia edulis, Gracilaria salicornia, Stypopodium zonale and Avrainvillea erecta in both quadrats along the line transects and random quadrats. In Tanjung Adang Laut shoal there were a temporary shift of plant population from a decline in seagrass to an increase or mass proliferation of specific macroalgae species, e.g., A. fragilissima, H. edulis and G. salicornia, which suggests the influence of increased development pressures and environmental disturbance in the nearby area.